KONSEP ASURANSI DALAM KONSTRUKSI BISNIS ISLAM (Kajian Reflektif Perspektif Fikih Muamalah) - Moh Nafih (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2013)
Application of equilibrium principal in Islam very is suggested, to be comprehended as life balance in world and eternity which must be carried by entrepreneur of moslem in this bearing ( Insurance). Hence this balance concept, inviting to all entrepreneur of moslem to be able to realize actions in business which can place x’self a others and moslem prosperity of life safety and world eternity.Other side, in have business to oblige the existence of business ethics Islamly which is put down above values of normatifias religion. Ethics is ideal moral values which must be applied in Islam business as business identity which have Islam bases. Business of Islam is the way of have business which clear of manipulation actions, exploitation, andfrom goods of lap. But most principal in characteristic have business of Islam conducted on the basis of is voluntary (antaradhin) and accepting each other between one another. So that from conducting business transaction it in an optimal fashion.In this ” concerning insurance”, representing new problem to Islam, and have the character of ijtihad, which must be tilled by moslem intelectuals to be able to know law status, operational procedure, and elementary principle of Islam, and also can be applied by society.